Regional potter interpretations: Case Study of synergic outcomes in master’s in Design and Product Development - Sampaio, João (2019)
Designers are key players in the process of cultural heritage interpretation and appropriation applied to other forms of production and expression in contemporary societies. In the academic training in masters of product design, knowledge creation through research as well public demonstrations of how this theoretical body is applied is quite relevant. These demonstrations allow the design to step up towards society and to show its capacity to add value and support decay activities, framing them into contemporary society and held it relevance in regional identity and economics. This article reports the outcomes of a synergic approach between master (MA) students, a museological institution and regional pottery artisans, in the development of terracotta tableware artefacts. In the designerly ways of knowing [1] a common concern is how design research and design education are contributing to the development of design as a discipline and how to reduce the gap between society and academy. Exploring a methodologic and co-creative approach of proposals, we help the students to develop a strategic and apply investigation to add value to regional and national pottery heritage and its contemporary use. By guiding them through defining what is (real context) and consequent deconstruction (abstract) of it, followed by exploration and construction of new scenarios of what could be. This approach is followed by the gap between analysis and synthesis, acting as bridge from the problem (knowing) to the solution (doing). With a more holistic and multidisciplinary approach, the students are trained to develop social and technical skills that place them into a working field and cooperation with several actors and stakeholders that increase research and learning skills through practical activities. On the other hand, the reconversion process of content and communication of practical research outcomes outside the academic field, supports the proximity between design and society (artisans, economic, cultural and governance actors), consolidates partnerships and collaborative processes.